Tacking: Nineteenth-Century Print Culture and its Readers - Brake, Laurel (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis article begins with an analysis of how nineteenth-century print journalism was produced to become a basic constituent of the public sphere of its day, and how it tackled the problems of survival beyond its date of issue. I then turn to the current flurry of remediation of the nineteenth-century press in the last five years and how digitisation of print now addresses similar tasks of optimising readership, distribution, and durability. This involves consideration of one of the current central questions, the roles of public and private platforms of delivery and their relation to access. In conclusion, I explore the impact of the digitisation of nineteenth-century journalism, and digitisation more generally, on Victorian studies and its publics. I focus on two aspects of impact: how meaning in literature and history is invigorated by digital access to their representation in historical and material context, and how the proliferation of illustration in new digital media, enabled by freedom from the limitations attached to print formats, addresses twenty-first century visually-literate readers directly, helping the transmission of Victorian Studies to the imagination of contemporary readers, across social class and internationally.